Curable composition and display device

By using a curable composition of hygroscopic particles composed of rare earth metal core and silane surface modified portion and (meth)acrylate resin in the encapsulated part of the OLED display device, the problem of insufficient hygroscopicity and optical performance of the encapsulated part in the prior art is solved, and efficient protection effect and excellent optical performance are achieved.

CN112592439BActive Publication Date: 2025-02-28LG DISPLAY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011043547.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-01
Filing Date
2020-09-28
Publication Date
2025-02-28
Estimated Expiration
2040-09-28

Smart Images

  • Figure CN112592439B_ABST
    Figure CN112592439B_ABST
Patent Text Reader

Abstract

Provided are a curable composition and a display device including hygroscopic particles having a metal core and a silane surface-modified portion attached to the metal core to provide an encapsulation portion having excellent moisture resistance and optical properties.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2019-0121696, filed on October 1, 2019, which is hereby incorporated by reference for all purposes as if fully set forth herein. Technical Field

[0003] Embodiments relate to a curable composition and a display device. Background Art

[0004] An organic electrical element is a device comprising one or more organic layers composed of organic materials, such as an organic light emitting diode (OLED), an organic solar cell, an organic photoreceptor or an organic transistor.

[0005] An organic light emitting device may be included in a display device. However, an organic layer included in the organic light emitting device may be very easily oxidized by external materials such as moisture or oxygen. The display device may include an encapsulation portion to prevent external materials such as moisture or oxygen from penetrating the organic electrical element.

[0006] Therefore, excellent hygroscopicity and optical properties are required in the encapsulation part to protect the organic electric element from external materials such as moisture or oxygen. Summary of the invention

[0007] The embodiment may provide a curable composition capable of forming an encapsulation portion having excellent hygroscopicity and optical properties.

[0008] Furthermore, the embodiment may provide a display device including an encapsulation part having excellent hygroscopicity and optical properties.

[0009] According to one aspect, embodiments may provide a curable composition including hygroscopic particles and a photocurable monomer.

[0010] The hygroscopic particle includes: a metal core including a rare earth metal; and a silane surface-modifying portion attached to the metal core.

[0011] The metal core may include a hydroxide of a rare earth metal.

[0012] The silane surface modification portion may be formed by a dehydration condensation reaction between a silane coupling agent and a rare earth metal.

[0013] The diameter of the hygroscopic particles may be between 1 nm and 100 nm.

[0014] The hygroscopic particle includes a partial structure represented by the following Chemical Formula 1 on the surface:

[0015] [Chemical formula 1]

[0016] Si(OX) a Y b

[0017] In Chemical Formula 1,

[0018] a and b are both integers from 1 to 3, a+b is 4,

[0019] X is the metal atom of the metal core,

[0020] Y is independently hydroxyl, C1-C 20 Alkyl, or C2-C 20 The alkenyl group, and

[0021] The alkyl group and the alkenyl group may be substituted with at least one of an propyleneoxy group, a methpropyleneoxy group, an amino group, a mercaptopropyleneoxy group, a mercaptomethpropyleneoxy group, and a glycidoxy group, respectively, or may be unsubstituted.

[0022] The photocurable monomer may include a (meth)acryloyl group.

[0023] According to another aspect, an embodiment may provide a display device including a substrate, an organic electric element on the substrate, and an encapsulation portion.

[0024] The encapsulation part includes hygroscopic particles, the encapsulation part is positioned on the peripheral part of the substrate and surrounds the side surface of the organic electric element. The hygroscopic particles include a rare earth metal core and a silane surface modification part connected to the metal core.

[0025] The encapsulating part further includes a (meth)acrylate resin.

[0026] The hygroscopic particles are dispersed in the (meth)acrylate resin.

[0027] The display device further includes: an encapsulation substrate facing the substrate; a color filter positioned on one surface of the encapsulation substrate; and a thin film transistor positioned on one surface of the substrate.

[0028] The display device further includes a passivation layer positioned to cover an upper portion and a side portion of the organic electric element.

[0029] A portion of the encapsulation portion is located on the passivation layer.

[0030] The display device further includes a filling resin that fills a gap between the organic electric element and the encapsulation substrate.

[0031] According to exemplary embodiments, a curable composition and a display device are provided, which include hygroscopic particles having a metal core and a silane surface modified portion connected to the metal core to provide an encapsulation portion having excellent anti-moisture properties and optical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above and other objects, features and advantages of the present disclosure will be more clearly understood by considering the following detailed description in conjunction with the accompanying drawings, in which:

[0033] Figure 1 is a view schematically showing hygroscopic particles according to an embodiment;

[0034] Figure 2 is a cross-sectional view of a display device according to an embodiment;

[0035] Figure 3 is a view for explaining an encapsulation portion of a display device according to an embodiment;

[0036] Figure 4 and Figure 5 is a SEM photograph of the lanthanum hydroxide particles prepared in Manufacturing Example 1;

[0037] Figures 6 to 10 is FT-IR spectroscopy, which is used to determine whether the surface of lanthanum hydroxide nanoparticles has been modified by silane coupling agents MPS and APTES;

[0038] Figures 11 to 13 is the thermogravimetric analysis (TGA) results of the lanthanum hydroxide nanoparticles and the hygroscopic nanoparticles according to Manufacturing Examples 1 and 2;

[0039] Fig.14 is a SEM photograph of lanthanum hydroxide nanoparticles prepared in Manufacturing Example 1;

[0040] Fig.15 is a SEM photograph of the hygroscopic nanoparticles prepared in Manufacturing Example 2 whose surfaces are modified with MPS;

[0041] Fig.16 is a SEM photograph of the hygroscopic nanoparticles prepared in Manufacturing Example 2 whose surfaces are modified with APTES;

[0042] Figures 17 to 19 are data for measuring optical properties of films prepared using the curable compositions of Examples 3 to 8 and Comparative Examples 1 to 4;

[0043] Fig. 20 is a cross-sectional view of a sample prepared for evaluating moisture resistance properties;

[0044] Fig.21is a view showing a color change of cobalt chloride paper encapsulated using the curable composition of Comparative Example 1;

[0045] Figure 22 to Figure 24 is a view showing color change of cobalt chloride paper encapsulated using the curable composition according to Examples 3 to 5; and

[0046] Figure 25 to Figure 27 : is a view showing the color change of the encapsulated cobalt chloride paper using the curable composition according to Examples 6 to 8. DETAILED DESCRIPTION

[0047] In the following description of examples or embodiments of the invention, reference will be made to the accompanying drawings in which specific examples or embodiments that may be implemented are shown by way of illustration, and in the accompanying drawings, the same reference numerals and symbols may be used to designate the same or similar components even when shown in different drawings from one another. In addition, in the following description of examples or embodiments of the invention, when it is determined that a detailed description of well-known functions and components incorporated herein may make the subject matter of some embodiments of the invention rather unclear, such detailed description will be omitted. Terms such as "including," "having," "comprising," "consisting of," "comprising," and "forming" as used herein are generally intended to allow for the addition of other components unless the term is used with the term "only." As used herein, the singular form is intended to include the plural form unless the context clearly indicates otherwise.

[0048] Terms such as "first", "second", "A", "B", "(A)" or "(B)" may be used herein to describe elements of the present invention. Each of these terms is not used to limit the nature, order, sequence or quantity of the elements, but is only used to distinguish the corresponding elements from other elements.

[0049] When it is mentioned that a first element is “connected or coupled”, “contacted or overlapped”, etc. with a second element, it should be interpreted that the first element may not only be “directly connected or coupled” or “directly contacted or overlapped” with the second element, but a third element may be “inserted” between the first element and the second element, or the first element and the second element may be “connected or coupled”, “contacted or overlapped”, etc. with each other via a fourth element, etc. Here, the second element may be included in at least one of the two or more elements that are “connected or coupled”, “contacted or overlapped”, etc. with each other.

[0050] When time relative terms (e.g., "after," "subsequently," "next," "before," etc.) are used to describe a process or operation of an element or construction, or a flow or step in an operation, treatment, or manufacturing method, these terms may be used to describe non-sequential or non-sequential processes or operations unless the terms "directly" or "immediately" are used together.

[0051] In addition, when referring to any scale, relative size, etc., it should be taken into account that the tolerance or error range included in the numerical value or corresponding information (such as level, range, etc.) of the element or feature may be caused by various factors (such as process factors, internal or external influences, noise, etc.), even if no relevant description is specified. In addition, the term "may" fully encompasses all meanings of the term "can".

[0052] The curable composition according to an embodiment includes hygroscopic particles and a photocurable monomer.

[0053] Figure 1 is a view schematically showing hygroscopic particles according to an embodiment.

[0054] refer to Figure 1 , the hygroscopic particle 100 includes a metal core 110 and a silane surface modified portion 120 .

[0055] The metal core 110 includes a rare earth metal. When the metal core 110 includes a rare earth metal, this may mean, for example, that the metal core 110 includes rare earth metal atoms.

[0056] The metal core 110 may include one or more selected from the group consisting of the following elements: lanthanum (La), scandium (Sc), yttrium (Y), cerium (Ce), neodymium (Nd), promethium (Pm), samarium (Sm), gadolinium (Gd), terbium (Tb), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu). When the metal core 110 includes a rare earth metal, the hygroscopic particles 100 have excellent hygroscopicity and may be transparent, so that the curable composition according to the embodiment may form an encapsulation portion having excellent hygroscopicity and optical properties.

[0057] The metal core 110 may include a hydroxide of a rare earth metal. For example, the metal core 110 may include one or more hydroxides selected from the group consisting of the following elements: lanthanum (La), scandium (Sc), yttrium (Y), cerium (Ce), neodymium (Nd), promethium (Pm), samarium (Sm), gadolinium (Gd), terbium (Tb), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu). When the metal core 110 includes a hydroxide of a rare earth metal, the metal core 110 may have a specific crystal structure, and the surface of the metal core 110 may be modified by a dehydration condensation reaction with a silane coupling agent including a silanol functional group.

[0058] As an example, the metal core 110 may include lanthanum hydroxide (La(OH) 3). When the metal core 110 includes lanthanum hydroxide (La(OH) 3), the hygroscopic particles 100 have excellent hygroscopicity and may be transparent, so that the curable composition according to the embodiment may form an encapsulation portion having excellent hygroscopicity and optical properties.

[0059] The silane surface modifying portion 120 is connected to the metal core 110. The connection of the silane surface modifying portion 120 to the metal core 110 may mean, for example, that the silane surface modifying portion 120 forms an XO—Si bond. At this time, the rare earth metal atom included in the metal core 110 is indicated by X.

[0060] For example, Figure 1 (a) to (c) schematically illustrate various aspects in which the silane surface modifying portion 120 is connected to the metal core 110 . Figure 1 (a) shows an example in which the Si element of the silane surface modifying portion 120 and the rare earth metal atom X of the metal core 110 are connected through one “—O—” bond. Figure 1 (b) shows an example in which the Si element of the silane surface modifying portion 120 and the rare earth metal atom X of the metal core 110 are connected through two “—O—” bonds. Figure 1 (c) shows an example in which the Si element of the silane surface modification part 120 and the rare earth metal atom X of the metal core 110 are connected by three "-O-" bonds. The hygroscopic particles contained in the curable composition can be mixed with Figure 1 The aspects shown in (a) to (c) are mixed.

[0061] The silane surface modification part 120 can be formed by the dehydration condensation reaction between the silane coupling agent and the rare earth metal. For example, when the above-mentioned silane coupling agent includes a hydroxyl group, and the metal core 110 includes a hydroxide of a rare earth metal atom X, the silane surface modification part 120 can be formed by the dehydration condensation reaction between the hydroxyl groups of the metal core 110 and the silane coupling agent. The dehydration condensation reaction can be performed, for example, under acidic conditions. The surface of the metal core 110 connected to the silane coupling agent by the dehydration condensation reaction can be referred to as the surface modification of the metal core 110. The metal nanoparticles can have condensation between the particles and degrade the expected physical properties. However, when the surface of the metal core 110 is modified by the silane coupling agent as described above, the dispersibility of the metal core 110 can be improved.

[0062] The type of silane coupling agent that can be used to modify the surface of the metal core 110 is not particularly limited as long as it can improve the dispersibility of the metal core 110. For example, the silane coupling agent is one or more selected from the group consisting of 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxymethyltriethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptoacryloxypropyltrimethoxysilane, 3-mercaptoacryloxypropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, N-phenylaminopropyltriethoxysilane, and hexamethyldisilazane.

[0063] The hygroscopic particles 100 may be nanoparticles. The diameter of the hygroscopic particles 100 may be 1 nm to 100 nm. The lower limit of the diameter of the hygroscopic particles 100 may be, for example, 3 nm or more or 5 nm or more. The upper limit of the diameter of the hygroscopic particles 100 may be, for example, 50 nm or less or 30 nm or less. In the present specification, the diameter of the hygroscopic particles 100 may refer to the diameter of the hygroscopic particles 100 observed by a scanning electron microscope (SEM).

[0064] When the diameter of the hygroscopic particles 100 satisfies the above range, the curable composition according to the embodiment may form an encapsulation part having excellent hygroscopicity and excellent optical properties.

[0065] The hygroscopic particle includes a partial structure represented by the following Chemical Formula 1 on the surface.

[0066] [Chemical formula 1]

[0067] Si(OX) a Y b

[0068] In Chemical Formula 1, a and b are both integers from 1 to 3, and a+b is 4.

[0069] In Chemical Formula 1, X is a metal atom of the metal core 100 .

[0070] In Chemical Formula 1, Y is independently hydroxyl, C1-C 20 Alkyl, or C2-C 20 The alkyl group and the alkenyl group may be substituted with at least one of an propyleneoxy group, a methpropyleneoxy group, an amino group, a mercaptopropyleneoxy group, a mercaptomethpropyleneoxy group and a glycidoxy group, respectively, or may not be substituted.

[0071] The partial structure represented by Chemical Formula 1 may be a partial structure constituting the silane surface modifying portion 120. Since the hygroscopic particle 100 includes the partial structure represented by Chemical Formula 1, the surface of the metal core 110 is modified so that the hygroscopic particle 100 may have excellent dispersibility.

[0072] A photocurable monomer may refer to a monomer that forms a polymer by initiating a polymerization reaction by irradiation with light. A photocurable monomer may refer to a monomer that can be cured by initiating a reaction by free radicals or cations, which are formed by irradiating with active energy rays (such as ultraviolet rays and electron beams).

[0073] The photocurable monomer may be a monomer having a functional group capable of initiating a polymerization reaction and being cured by irradiation with light. The photocurable monomer may be, for example, a monomer that can be cured by ultraviolet light having a wavelength of 300 nm to 500 nm.

[0074] For example, the photocurable monomer may include a functional group including an unsaturated double bond similar to vinyl such as acryloyl, methacryloyl, acryloyloxy or methacryloyloxy, or a functional group such as epoxy or oxetane. In an exemplary example, the photocurable monomer may include a (meth)acryloyl group. (Meth)acryloyl may be referred to as one of acryloyl, methacryloyl, and a combination thereof.

[0075] The photocurable monomer may satisfy Chemical Formula 2 below.

[0076] [Chemical formula 2]

[0077]

[0078] In Chemical Formula 2, R1 is hydrogen or a C1-C4 alkyl group, n is an integer of 2 or more, and X may be a linear, branched or cyclic alkyl or alkenyl group or a mixture thereof.

[0079] For example, X could be C3-C 30 Alkyl, C4-C 28 Alkyl, C6-C 28 Alkyl, C8-C 22 Alkyl or C 12 -C 20 In addition, X can be C3-C 30 Alkenyl, C4-C 28 Alkenyl, C6-C 28 Alkenyl, C8-C 22 Alkenyl or C 12 -C 20 The alkenyl group.

[0080] The above-mentioned photocurable monomer can be, for example, one or more selected from the group consisting of: methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, trimethylolpropane tri(meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, pentaerythritol tri(meth)acrylate, ethylene glycol di(meth)acrylate and 2-ethylhexyl (meth)acrylate.

[0081] In a curable composition of one example, 0.1 to 5 parts by weight of hygroscopic particles may be included, and 90 to 99.9 parts by weight of photocurable monomers may be included. In another example of a curable composition, 0.1 to 3 parts by weight of hygroscopic particles may be included, and 90 to 99.9 parts by weight of photocurable monomers may be included. In another example of a curable composition, 0.1 to 2 parts by weight of hygroscopic particles may be included, and 90 to 99.9 parts by weight of photocurable monomers may be included. When the curable composition includes hygroscopic particles and photocurable monomers in the above-mentioned weight ratio, the curable composition provides a transparent encapsulation portion with low haze and excellent hygroscopicity.

[0082] In an embodiment, the photocurable composition may include an initiator. The initiator may be, for example, a photopolymerization initiator. As the photopolymerization initiator, for example, a cationic photopolymerization initiator may be used.

[0083] As the cationic photopolymerization initiator, an ionized cationic initiator based on an onium salt or an organic metal salt, or a non-ionized cationic photopolymerization initiator based on an organic silane or a latent sulfonic acid can be used. The initiator based on the onium salt can be a diaryliodonium salt, a triarylsulfonium salt or an arylazo salt, the initiator based on the organic metal salt can be an aromatic hydrocarbon, the initiator based on the organic silane can be an o-nitrobenzyl triarylsilyl ether, a triarylsilyl peroxide or an acylsilane, and the initiator based on the latent sulfonic acid can be an α-sulfonyloxy ketone or an α-hydroxymethylbenzoin sulfonate, but the present application is not limited thereto.

[0084] The above-mentioned initiator can be, for example, a free radical initiator. For example, a benzoin-based, hydroxyketone-based, aminoketone-based or phosphine oxide-based photoinitiator can be used, and specifically, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholine-propane-1-one, 4-(2-hydroxyethoxy)phenyl ketone can be used. 1-[4-(1-methylvinyl)phenyl]propanone], or 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide.

[0085] The content of the initiator in the curable composition can be changed by the type and content ratio of the polymerizable functional group included in the curable composition or the crosslinking density of the polymer formed by the curable composition. For example, the initiator can be included in the curable composition in an amount of 0.1 to 10 parts by weight relative to 100 parts by weight of the photocurable monomer.

[0086] Other embodiments may provide a display device including the above-described curable composition.

[0087] Figure 2 is a cross-sectional view of a display device according to an embodiment.

[0088] refer to Figure 2 , the display device 200 according to the embodiment includes a substrate 210 , an organic electric element 220 , and an encapsulation part 230 .

[0089] There is no particular limitation on the type of substrate 210 as long as the organic electrical element 220 and the thin film transistor for driving the organic electrical element 220 can be formed. For example, the substrate 210 may be a plastic substrate or a glass substrate. In addition, the thin film transistor for driving the organic electrical element 220 may be positioned on one surface of the substrate 210.

[0090] The organic electric element 220 may be located on the substrate 210. For example, the organic electric element 220 may be located on a thin film transistor (not shown) on one surface of the substrate 210.

[0091] The organic electrical element 220 may be, for example, an organic light emitting diode (OLED). The organic light emitting diode may include a first electrode, an organic layer, and a second electrode stacked in sequence. For example, the first electrode may be an anode electrode, and the second electrode may be a cathode electrode.

[0092] The organic electrical element 220 may be located in an active area (A / A) of the display device to transmit visual information. The non-active area (N / A) may be located in a peripheral portion of the display device. Wires for driving the organic electrical element 220 may be located in the non-active area.

[0093] The encapsulation part 230 includes hygroscopic particles. The hygroscopic particles include a rare earth metal core and a silane surface modification part connected to the metal core. Unless otherwise described for the display device according to the embodiment, the hygroscopic particles of the display device 200 according to the embodiment are substantially the same as the subject matter of the hygroscopic particles contained in the curable composition according to the above-mentioned embodiment.

[0094] The encapsulation part 230 is positioned on the peripheral portion of the substrate 210 and surrounds the side surface of the organic electric element 220. Since the organic electric element 220 emits light so that the display device 200 can transmit visual information, it can be located in the active area (A / A) of the display device. The encapsulation part 230 can be positioned on the peripheral portion of the substrate 210 to surround the organic electric element 220 in the central portion of the substrate 210. Therefore, the encapsulation part 230 can prevent external materials such as oxygen or moisture from entering the organic electric element 220 positioned in the center of the substrate 210 from the outside of the display device 200.

[0095] The display device 200 may further include an encapsulation substrate 240 facing the substrate 210. An encapsulation layer for encapsulating the organic electric element 220 may be located on one surface of the encapsulation substrate 240. In addition, a color filter (not shown) is located on one surface of the encapsulation substrate 240 to convert the wavelength of light emitted from the organic electric element 220.

[0096] The type of the encapsulation substrate 240 is not particularly limited, and for example, a plastic substrate, a glass substrate, or a metal thin film substrate may be used.

[0097] The display device 200 may further include a passivation layer 250. The passivation layer 250 is not particularly limited as long as it can protect the organic electric element 220 and the thin film transistor located below the organic electric element 220, but the passivation layer 250 may be, for example, an inorganic layer.

[0098] The passivation layer 250 may be positioned to cover the upper portion and the side portion of the organic electrical element 220. For example, the passivation layer 250 may be formed by plasma enhanced chemical vapor deposition (PECVD). When the passivation layer 250 is formed by PECVD, the passivation layer 250 may be formed along the surface of the upper portion and the side portion of the organic electrical element 220. Since the passivation layer 250 is positioned to cover the upper portion and the side portion of the organic electrical element 220, moisture and oxygen may be effectively prevented from penetrating the organic electrical element 220.

[0099] A portion of the encapsulation portion 230 may be located on the passivation layer 250. Figure 2 As shown, a portion of the passivation layer 250 may be located below the encapsulation portion 230, and a portion of the encapsulation portion 230 may be located on the passivation layer 250. After the organic electrical element 220 is formed on the substrate 210, the passivation layer 250 is formed to cover the upper portion and the side of the organic electrical element 220, and then the encapsulation portion 230 is formed, so that the above structure of the display device 200 can be implemented.

[0100] When a portion of the encapsulation part 230 is positioned on the passivation layer 250 , the frame of the display device 200 may be minimized, so that the aesthetics of the display device 200 is improved.

[0101] The encapsulation part 230 may further include an optically transparent base resin. Since the encapsulation part 230 includes transparent hygroscopic particles and an optically transparent base resin, it may be transparent while having excellent hygroscopicity.

[0102] The hygroscopic particles may be dispersed in the base resin. As described above, since the hygroscopic particles (including the silane surface modified portion) have excellent dispersibility, they may be easily dispersed in the base resin to prevent the encapsulation portion 230 from being discolored.

[0103] The base resin may be, for example, a (meth)acrylate resin. The (meth)acrylate resin may refer to a resin formed by polymerizing a monomer including a (meth)acryloyl group.

[0104] For example, the (meth)acrylate resin that can be used as the base resin can be one or more selected from the group consisting of poly[methyl (meth)acrylate], poly[ethyl (meth)acrylate], poly[butyl (meth)acrylate], poly[trimethylolpropane tri(meth)acrylate], poly[2-hydroxyethyl (meth)acrylate], poly[2-hydroxypropyl (meth)acrylate], pentaerythritol tri(meth)acrylate, ethylene glycol di(meth)acrylate and 2-ethylhexyl (meth)acrylate.

[0105] The display device further includes a filling resin 260. The filling resin 260 may fill a gap between the organic electric element 220 and the encapsulation substrate 240.

[0106] The display device 200 according to the embodiment may be a display device in which the organic electric element 220 is encapsulated in a dam and fill method. The encapsulation portion 230 is located in a non-display area (N / A) of the display device 200 as a dam structure and surrounds the side of the organic electric element 220, and the filling resin 260 is used as a filling structure to fill the gap between the organic electric element 220 and the encapsulation substrate 240.

[0107] Since the filling resin 260 fills the gap between the organic electric element 220 and the encapsulation substrate 240 above the display area (A / A) of the display device 200, the type of the filling resin 260 is not particularly limited as long as it has excellent transparency. For example, the filling resin 260 may use (meth) acrylate resin or epoxy resin.

[0108] Figure 3 is a view for explaining an encapsulation portion of a display device according to an embodiment.

[0109] refer to Figure 3 , the encapsulation part 230 may include a (meth)acrylate resin 130, and the hygroscopic particles 100 may be dispersed in the (meth)acrylate resin 130. The hygroscopic particles 100 may be relatively uniformly dispersed in the (meth)acrylate resin 130 by including the silane surface modification part 120 connected to the metal core 110.

[0110] Since the hygroscopic particles 100 are relatively uniformly dispersed in the encapsulation part 230, the encapsulation part 230 can have excellent optical properties. When evaluated using a haze meter HM-150 according to ASTM D1003, the haze of the encapsulation part 230 can be 10% or less. The upper limit of the above haze range can be, for example, 9% or less, 7% or less, or 6% or less. The lower limit of the above haze range is not particularly limited, because the lower the haze value, the better the optical performance, but for example, it can be 0.1% or more, 0.2% or more, or 0.3% or more.

[0111] Since the hygroscopic particles 100 are relatively uniformly dispersed in the encapsulation part 230, the encapsulation part 230 can have excellent transmittance. The encapsulation part 230 can have a transmittance of 85% or more for light having a wavelength of 450nm, for example. The lower limit of the above transmittance range can be, for example, 87% or more, or 88% or more. The upper limit of the above transmittance range is not particularly limited because the higher the transmittance value, the better the optical property, but can be, for example, 99.9% or less, or 99% or less.

[0112] Hereinafter, the hygroscopic particles 100 and the display device 200 according to the embodiment will be described in more detail through the following examples, but the scope of the present invention is not limited thereto.

[0113] Manufacturing Example 1. Preparation of lanthanum hydroxide (La(OH)3) nanoparticles

[0114] A precursor mixture was prepared by stirring 0.14 g of La(NO 3 ) 3 ·6H 2 O (Fluka, 99%) as a precursor and 0.29 g of citric acid represented by Chemical Formula 3 in 20 mL of distilled water.

[0115] [Chemical formula 3]

[0116]

[0117] 1g potassium hydroxide (KOH) was dissolved in 10mL ethanol and then added to the precursor mixture to prepare a mixed solution. The prepared mixed solution was stirred at room temperature for 1 hour (600rpm / 1h). The stirred mixed solution was transferred to a Teflon-lined container and then reacted in a microwave (180°C / 1h). After the reaction, the resulting precipitate was centrifuged with ethanol and double distilled water and purified twice at 5,000rpm / 10 minutes, and then dried at 80°C for 6 hours.

[0118] According to the above-mentioned manufacturing example, the following reaction is performed to produce lanthanum hydroxide (La(OH) 3 ).

[0119] La(NO3)3·6H2O+3KOH→La(OH)3+3KNO3+6H2O

[0120] La2O3+3H2O→2La(OH)3

[0121] Figure 4 and Figure 5 is a SEM photograph of the lanthanum hydroxide particles prepared in the above-mentioned manufacturing example 1. Figure 4 and Figure 5 , it can be seen that the diameter of the lanthanum hydroxide (La(OH) 3 ) nanoparticles prepared in Manufacturing Example 1 is about 10 to 20 nm.

[0122] Manufacturing Example 2. Surface modification of lanthanum hydroxide (La(OH)3) nanoparticles

[0123] Ethanol and distilled water were added to prepare 25 mL of a mixed solution. 0.1 mL of acetic acid was added to the mixed solution to adjust the pH to 3.5.

[0124] Before mixing the solution, 0.12 g of the lanthanum hydroxide nanoparticles prepared in Manufacturing Example 1 and 0.24 g of a silane coupling agent were added and stirred for 3 hours to prepare hygroscopic particles. As the silane coupling agent, 3-(trimethoxysilyl)propyl methacrylate (MPS) was used in Example 1, and 3-aminopropyltriethoxysilane (APTES) was used in Example 2.

[0125] Figures 6 to 10 is FT-IR spectrum to determine whether the surface of lanthanum hydroxide nanoparticles has been modified by silane coupling agents MPS and APTES.

[0126] Figure 6 is the FT-IR spectrum of the lanthanum hydroxide (La(OH) 3 ) nanoparticles prepared in Manufacturing Example 1.

[0127] Figure 7 : is the FT-IR spectrum of MPS as the silane coupling agent used in Production Example 2.

[0128] Figure 8 is the FT-IR spectrum of the hygroscopic particles prepared in Manufacturing Example 2 whose surfaces are modified with MPS.

[0129] Fig. 9 FT-IR spectrum results of APTES used in Production Example 2 as a silane coupling agent.

[0130] Fig.10 is the FT-IR spectrum of the hygroscopic particles prepared in Manufacturing Example 2 whose surfaces are modified with APTES.

[0131] refer to Figures 6 to 8 ,exist Figure 8 observed at 1720 cm -1 The peak at Figure 6 Peaks not observed in . Figure 7 , since this peak refers to the C═O bond included in MPS, it can be seen that hygroscopic particles including a silane surface-modified portion including a C═O bond derived from MPS are formed through the process of Manufacturing Example 2.

[0132] refer to Figure 6 , Fig. 9 and Fig.10 ,exist Fig.10 observed at 2932cm -1 The peak at Figure 6 Peaks not observed in . Fig. 9 , since this peak represents the CH bond included in APTES, it can be seen that hygroscopic particles including a silane surface modified portion including a CH bond derived from APTES are formed through the process of Manufacturing Example 2.

[0133] Experimental Example 1. Dispersion of Hygroscopic Particles in Resin and Evaluation of Optical Properties of Resin Film Including Hygroscopic Particles

[0134] 0.05 g of the hygroscopic nanoparticles of Example 1, 4.95 g of a (meth)acrylate monomer, and a UV curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Example 3).

[0135] 0.10 g of the hygroscopic nanoparticles of Example 1, 4.90 g of a (meth)acrylate monomer, and a UV curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Example 4).

[0136] 0.25 g of the hygroscopic nanoparticles of Example 1, 4.75 g of a (meth)acrylate monomer, and a UV curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Example 5).

[0137] 0.05 g of the hygroscopic nanoparticles of Example 2, 4.95 g of a (meth)acrylate monomer, and a UV curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Example 6).

[0138] 0.10 g of the hygroscopic nanoparticles of Example 2, 4.90 g of a (meth)acrylate monomer, and a UV curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Example 7).

[0139] 0.25 g of the hygroscopic nanoparticles of Example 2, 4.75 g of a (meth)acrylate monomer, and a UV curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Example 8).

[0140] 5.00 g of a (meth)acrylate monomer and a curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Comparative Example 1).

[0141] 0.05 g of the lanthanum hydroxide nanoparticles of Manufacturing Example 1, 4.95 g of a (meth)acrylate monomer, and an ultraviolet curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Comparative Example 2).

[0142] 0.10 g of the lanthanum hydroxide nanoparticles of Manufacturing Example 1, 4.90 g of a (meth)acrylate monomer, and an ultraviolet curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Comparative Example 3).

[0143] 0.25 g of the lanthanum hydroxide nanoparticles of Manufacturing Example 1, 4.75 g of a (meth)acrylate monomer, and an ultraviolet curing initiator were mixed at 1% by weight and then stirred to prepare a curable composition (Comparative Example 4).

[0144] Figures 11 to 13 are thermogravimetric analysis (TGA) results of the lanthanum hydroxide nanoparticles and the hygroscopic nanoparticles according to Manufacturing Examples 1 and 2.

[0145] Fig.11 is the TGA result of the lanthanum hydroxide nanoparticles prepared in Manufacturing Example 1, Fig.12 is the TGA result of the hygroscopic particles whose surfaces are modified with MPS prepared in Manufacturing Example 2, and Fig.13 : is the TGA result of the hygroscopic particles prepared in Manufacturing Example 2, the surfaces of which are modified with APTES.

[0146] refer to Figures 11 to 13 , it can be seen that when comparing the mass change due to the temperature rise after the surface modification reaction with the mass change before the surface modification reaction at 700°C, the difference in mass change according to the surface modification reaction by MPS and APTES is 6% (see Fig.10 ) and 5.5% (see Fig.11 ). This difference may be due to the mass of the reactant bound to the surface of the lanthanum hydroxide nanoparticles as a result of the surface modification of the lanthanum hydroxide nanoparticles prepared in Manufacturing Example 1 according to Manufacturing Example 2.

[0147] Fig.14 is a SEM photograph of lanthanum hydroxide nanoparticles prepared in Manufacturing Example 1.

[0148] Fig.15 is a SEM photograph of the hygroscopic nanoparticles prepared in Preparation Example 2, the surfaces of which are modified with MPS.

[0149] Fig.16 is a SEM photograph of the hygroscopic nanoparticles prepared in Preparation Example 2, the surfaces of which are modified with APTES.

[0150] refer to Fig.14 and Fig.15 , it can be seen that even when the surface modification was performed under acidic conditions of pH 3.5, the nanoparticles did not undergo morphological changes. Fig.14 and Fig.16 , it can be seen that the nanoparticles did not undergo morphological changes even when the surface modification was performed under acidic conditions of pH 3.5. Therefore, it can be expected that properties such as the quantum confinement effect of lanthanum hydroxide nanoparticles due to the surface modification will be maintained even in surface-modified hygroscopic nanoparticles.

[0151] Figures 17 to 19 are data for measuring optical properties of films prepared using the curable compositions of Examples 3 to 8 and Comparative Examples 1 to 4.

[0152] After the curable compositions of Examples 3 to 8 and Comparative Examples 1 to 4 were coated by bar coating and then cured with a UV lamp, Figures 17 to 19 The films for measuring optical properties were formed to a thickness of 10 μm.

[0153] refer to Fig.17 , it can be seen that Comparative Example 1 not including lanthanum hydroxide has the highest permeability, and its permeability decreases as the content of lanthanum hydroxide increases.

[0154] refer to Fig.18 , it can be seen that Comparative Example 1 not including hygroscopic particles has the highest permeability, and its permeability decreases as the content of hygroscopic particles whose surfaces are modified by MPS increases.

[0155] refer to Fig.19 , it can be seen that Comparative Example 1 not including hygroscopic particles has the highest permeability, and its permeability decreases as the content of hygroscopic particles whose surfaces are modified by APTES increases.

[0156] Table 1 below shows Figures 17 to 19 result.

[0157] [Table 1]

[0158]

[0159]

[0160] Although Comparative Example 1 is measured as the highest permeability, it does not include hygroscopic particles, and therefore, the anti-humidity property is very poor as a result of the anti-humidity property test described below. On the other hand, it can be seen that Examples 3 to 8 include hygroscopic particles, and therefore, they can have more excellent hygroscopicity, better light transmittance and haze properties than Comparative Examples 2 to 4.

[0161] Experimental Example 2. Evaluation of anti-moisture properties of a resin including nanoparticles

[0162] The cobalt chloride paper used for measuring moisture permeation was dried at 100° C. for 1 hour and then placed on a glass substrate.

[0163] Fig. 20 is a cross-sectional view of a sample prepared to evaluate moisture resistance.

[0164] refer to Fig. 20, the curable compositions of Examples 3 to 8 and Comparative Example 1 were applied to a glass cell having a gap of 2 mm to seal the cobalt chloride paper.

[0165] When using ultraviolet light (300mW / cm 3 ) After the portion coated with the curable composition is cured for 1 minute, Fig. 20 The samples shown were placed on a thermo-hygrostat with a temperature of 85° C. and a relative humidity of 85%.

[0166] Fig.21 : is a view showing the color change of the cobalt chloride paper encapsulated using the curable composition of Comparative Example 1.

[0167] Figure 22 to Figure 24 : is a view showing the color change of the cobalt chloride paper encapsulated using the curable composition according to Examples 3 to 5.

[0168] refer to Figure 21 to Figure 24 , we can see that in Fig.21 In the embodiment of the present invention, the color of the cobalt chloride paper encapsulated with the curable composition of Comparative Example 1 not including the hygroscopic particles changes after 24 hours (24h), but the color of the cobalt chloride paper encapsulated with the curable composition of Examples 3 to 5, which includes lanthanum hydroxide nanoparticles whose surfaces are modified by MPS, fades after as little as 48 hours and as long as 120 hours. Therefore, it can be seen that the curable composition including the hygroscopic nanoparticles whose surfaces are modified by MPS provides an encapsulation part with more excellent moisture resistance.

[0169] Figure 25 to Figure 27 : is a view showing the color change of the encapsulated cobalt chloride paper using the curable composition according to Examples 6 to 8.

[0170] refer to Fig.21 and Figure 25 to Figure 27 , it can be seen that in Fig.21 In the embodiment, the color of the cobalt chloride paper encapsulated with the curable composition of Comparative Example 1 not including the hygroscopic particles changes after 24 hours (24h), but the color of the cobalt chloride paper encapsulated with the curable composition of Examples 6 to 8 fades after as short as 48 hours and as long as 144 hours, wherein the curable composition of Examples 6 to 8 includes lanthanum hydroxide nanoparticles whose surfaces are modified by APTES. Therefore, it can be seen that the curable composition including the hygroscopic nanoparticles whose surfaces are modified by APTES provides an encapsulation part having more excellent moisture resistance.

[0171] The above description has been given to enable any person skilled in the art to implement and use the technical ideas of the present invention, and the above description has been provided in the context of specific applications and their requirements. Various modifications, additions and substitutions to the described embodiments will be apparent to those skilled in the art, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present invention. The above description and accompanying drawings provide examples of the technical ideas of the present invention for illustrative purposes only. That is, the disclosed embodiments are intended to illustrate the scope of the technical ideas of the present invention. Therefore, the scope of the present invention is not limited to the embodiments shown, but conforms to the widest scope consistent with the claims. The scope of protection of the present invention should be interpreted based on the following claims, and all technical ideas within the scope of its equivalents should be interpreted as being included within the scope of the present invention.

Claims

1. A curable composition comprising: A hygroscopic particle comprising: a metal core comprising a rare earth metal and a silane surface modification portion attached to the metal core; and Photocurable monomers, Wherein, the silane surface modification part is formed by a dehydration condensation reaction between a silane coupling agent and the rare earth metal, wherein the metal core comprises a hydroxide of the rare earth metal, wherein the curable composition comprises 0.1 to 2 parts by weight of the hygroscopic particles and 90 to 99.9 parts by weight of the photocurable monomer, The silane coupling agent is one or more selected from the group consisting of: 3-(trimethoxysilyl)propyl methacrylate (MPS) and 3-aminopropyltriethoxysilane (APTES).

2. The curable composition according to claim 1, wherein The metal core includes one or more selected from the group consisting of lanthanum (La), scandium (Sc), yttrium (Y), cerium (Ce), neodymium (Nd), promethium (Pm), samarium (Sm), gadolinium (Gd), terbium (Tb), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu).

3. The curable composition according to claim 1, wherein The diameter of the hygroscopic particles is 1 nm to 100 nm.

4. The curable composition according to claim 1, wherein The photocurable monomer includes a (meth)acryloyl group.

5. The curable composition according to claim 1, further comprising an initiator.

6. A display device, comprising: substrate; an organic electrical element located on the substrate; as well as an encapsulation portion, the encapsulation portion comprising: hygroscopic particles including a metal core containing a rare earth metal and a silane surface modification portion connected to the metal core, and the encapsulation portion is positioned on a peripheral portion of the substrate and surrounds a side surface of the organic electric element, Wherein, the silane surface modification part is formed by a dehydration condensation reaction between a silane coupling agent and the rare earth metal, wherein the metal core comprises a hydroxide of the rare earth metal, The silane coupling agent is one or more selected from the group consisting of: 3-(trimethoxysilyl)propyl methacrylate (MPS) and 3-aminopropyltriethoxysilane (APTES).

7. The display device according to claim 6, wherein: The encapsulation part further comprises a (meth)acrylate resin, and The hygroscopic particles are dispersed in the (meth)acrylate resin.

8. The display device according to claim 7, wherein: The encapsulated portion has a haze of 10% or less.

9. The display device according to claim 7, wherein: The encapsulating portion has a transmittance of 85% or more with respect to light having a wavelength of 450 nm.

10. The display device according to claim 7, further comprising: an encapsulation substrate facing the substrate, a color filter on one surface of the encapsulation substrate, and a thin film transistor on one surface of the substrate.

11. The display device according to claim 10, further comprising a passivation layer positioned to cover an upper portion and a side portion of the organic electric element, and in, A portion of the encapsulation portion is located on the passivation layer. 12 . The display device according to claim 10 , further comprising a filling resin filling a gap between the organic electric element and the encapsulation substrate.

Citation Information

Patent Citations

  • Treating agent for insect bite containing glechoma grandis extract

    KR1020190121696A

  • Organic light emiting device and method of manufacturing the same

    CN1992371A